Synergistic surface engineering enables high-efficiency and stable operation of low-bromine wide-bandgap perovskite solar cells - Zhenzhen Peng; Zhimin Fang; Yi Zhang; Rongyao Lv; Yu-Ang Liu; Dehan Li; Bairu Li; Luozheng Zhang; Shuang Chen; Shangfeng Yang; Jianning Ding (Chemical Engineering Journal, 2026)

Zinc co-exposure with different antibiotic classes drives distinct microbial community restructuring in activated sludge - Yu Ang Li; Shijie Dong; Yongchao Li; Wei Wen; Mengbo Yuan; Jiangxiao Luo; Bin Shi; Renxin Zhao (Journal of Hazardous Materials, 2026)

A multifunctional polar additive enables highly reversible zinc anodes via synergistic regulation of water chemistry, deposition behavior, and interphase stability - Yufei Wang; Pengtao Wang; Ang Li; Ce Liang; Kaifeng Yu (Chemical Engineering Journal, 2026)

METTL18-catalyzed histidine methylation of YTHDF2 promotes mRNA stability - Wen-Lan Yang; Meng-Xia Liu; Yue Han; Xing-Xing Li; Ye Gu; Xinyuan Tian; Mengqian Mu; Xiaolin Zhang; Yanzhe Wang; Xinyu Li; Yu-Sheng Chen; Chun-Chun Gao; et al. (Science China Life Sciences, 2026)

Delta-Band Dynamics of CaMKI-Positive Preoptic Neurons Encode Thermal Homeostatic Information - Dian-Dian Wang; Run-Zhou Yang; Song-Tang Sun; Ya-Lun Sun; Rui-Yu Wang; Xiao-Yan Meng; Sen-Miao Li; Jia-Kang Li; Pei-Pei Liu; Shu-Ang Li; Jian-Sheng Kang (Neuroscience Bulletin, 2026)

Effects of age-related gastrointestinal conditions on the digestion of myofibrillar protein-stabilized fish oil oleogel emulsions - Yumin Niu; Li Hu; Zongyuan Han; Hongli Wang; Yu-ang Jiang; Xueyan Cao; Jun-Hua Shao (Food Research International, 2026)

A sensory-calibrated electronic nose method for odor intensity quantification and grade identification in refrigerators - Shiwen Cheng; Li’ang Yin; Xiao Ye; Xiaozheng Liu; Yumei Qin; Yaqing Song; Suyun Zhang; Tengfei Yu; Chonghui Zhang; Shiyi Tian (Food Research International, 2026)

Designing hard-soft carbon composite anodes via a normalized pore volume-mass matching strategy for high-performance sodium storage - Xiaoqi Yu; Xiaoyu Xu; Hanyu Wei; Xiaofeng Zhang; Haiyan Liu; Chengwei Fan; Ang Li; Xiaohong Chen; Huaihe Song (Chemical Engineering Journal, 2026)

Microbial community shift and functional reorganization from influent to effluent in wastewater treatment plants on the Qinghai–Tibet Plateau - Yongchao Li; Bin Shi; Di Li; Yu-Ang Li; Mengbo Yuan; Jiangxiao Luo; Shijie Dong; Wei Wen; Renxin Zhao (Journal of Environmental Management, 2026)

Tailored self-assembled molecule for efficient charge extraction and enhanced crystallization in wide-bandgap perovskite solar cells - Haojun Hu; Xianglang Sun; Xuke Yang; Zongbao Li; Peiyan Zhang; Xinyu Yu; Shi'ang Li; Zifan Lin; Dayu Liu; Ziyang He; Chuyun Deng; Longhui Zeng; et al. (Chemical Engineering Journal, 2026)

Serum Endogenous Opioid Levels are Associated with Self-Injury Severity in Adolescents with Non-Suicidal Self-Injury and Comorbid Depression - Jin-Jun Ding; Xiao-Li Liu; Ang Li; Yi-Yao Liang; Yu-Bo Wang; Xiao-Na Zhu; Jie Li; Jie Weng; Lan Yan; Wen-Wen Duan; Zi-Chen Zhang; Ti-Fei Yuan; et al. (Neuroscience Bulletin, 2026)

The dual nature of neuroticism: distinct dimensions impact longevity and well-being - Yini He; Jing Xiao; Ke Hu; Tian Gao; Yan Yan; Yu Yu; Lei Wang; Kaixin Li; Wenkun Lei; Kun Zhao; Changsheng Dong; Xiaohan Tian; et al. (Science Bulletin, 2026)

The DNA-binding protein PfAP2-V regulates erythrocyte invasion and pathogenesis of the human malaria parasite Plasmodium falciparum - Yanxin Zhang; Changhong Wang; Qilong Li; Ang Li; Yutao Zhang; Ziwei Su; Liying Yu; Kexin Zheng; Tong Liu; Ning Jiang; Yiwei Zhang; Xiaoyu Sang; et al. (Science China Life Sciences, 2026)

Isolation and identification of spoilage bacteria from kiwifruit and analysis of the antagonistic activity of three Bacillus strains against these bacteria - Ang Liu; Wen-xin Li; Yi Liu; Xing-lin Ran; Bo-yu Dong; Qiu-ping Yao; De-quan Zhu (Food Control, 2026)

Unlocking microbial synergy in microalgae-bacteria granules: RSM-driven optimization and lifecycle microbial metagenomics for high-ammonia wastewater treatment - Yanni Geng; Chun-Ang Lian; Liming Yang; Spyros G. Pavlostathis; Xuejiao Qiao; Zhiguang Qiu; Yu Wang; Nan Dong; Anjie Li; Xubiao Luo; Ke Yu (Water Research, 2026)

Superoxide mediated Mn(II) oxidation of an alkali-tolerant bacterium Pseudorhizobium flavum MXJ-1 - Haixia Pan; Fei Li; Ruiying Zhang; Yu Liu; Jieyi Li; Tongtong Wu; Ang Li; Hao Zhou (Journal of Environmental Sciences, 2026)

Impact and assessment of hydraulic rake trawling on benthic communities in Urechis unicinctus aquaculture zones, Laizhou Bay, China - Yuze Tang; Erwann Legrand; Jiaqi Li; Haiqing Wang; Ang Li; Lulei Liu; Zirong Liu; Suyan Xue; Shoutuan Yu; Yuze Mao (Ocean & Coastal Management, 2026)

Characteristics and controlling factors of stable isotopes in precipitation based on 9-year monitoring data in the monsoon transition zone of the Tibetan Plateau - Wang Shao-yong; Wang Qiao-li; Kang Shi-chang; Ding Yong-jian; Xue Yu-ang; He Xiao-bo (Agricultural and Forest Meteorology, 2026)

Boosting the plateau capacity via phosphoric acid cross-linking strategy for phenolic resin-based hard carbon - Xiaoqi Yu; Xiaoyu Xu; Hanyu Wei; Haiyan Liu; Ang Li; Xiaohong Chen; Huaihe Song (Chemical Engineering Journal, 2025)

Cyanoalanine Synthase encoding gene SlCAS1 regulates tomato fruit ripening by modulating pigment metabolism and ethylene biosynthesis - Song-Li Han; Yu-Qi Zhao; Li-Xia Li; Pedro Garcia-Caparros; Yan-Hong Li; Zhen Wang; Yi-Ang Feng; Kang-Di Hu; Hua Zhang; Gai-Fang Yao (Postharvest Biology and Technology, 2025)

Effects of Per- and polyfluoroalkyl substances on atherosclerosis: an evidence-based risk assessment in the context of the TRAEC strategy - Yiming Zhu; Zhenzhen Tan; Ziwen An; Longfei Li; Mingmei Guo; Wenjing Duan; Zhixia Yu; Ziang Chen; Yi Liu; Ang Li; Huicai Guo (Environmental Research, 2025)

Revealing the ionic storage mechanisms of Mo2VC2Tz (MXene) in multiple aqueous electrolytes for high-performance supercapacitors - Xiaodie Xuan; Yangyang Xie; Yi Tang; Jianghong Zhou; Zhao Bi; Junhui Zou; Yu-ang Lei; Jiahang Gao; Lu Li; Aibo Zhang; Chenhui Yang (Chemical Engineering Journal, 2025)

Unraveling the mechanism of fouling mitigation in AGS-MBR system: From AGS properties to foulant interactions - Yu Jiang; Si Wang; Chaoyu Li; Yu-Ang Cai; Xiuquan Xiong; Yinghao Tang; Senlin Shao; Chuansheng Wang; How Yong Ng (Water Research, 2025)

High content of single-atomic sulfur in nano carbon spheres boosting potassium storage performance - Bin Cao; Zirong Guo; Huan Liu; Yu Ma; Wei Zhao; Yiheng Yang; Ang Li; Huaihe Song; Yaxiong Yang; Zhenglong Li; Wubin Du (Chemical Engineering Journal, 2025)

High-Voltage aqueous supercapacitors based on l-lysine pH Self-Buffering Coating-modified carbon cloth electrode - Ang Xu; Jie Gao; Huan Li; Xiyu Song; Bo Xu; Ying Liu; Yuanyuan Yu; Ping Wang; Qiang Wang; Man Zhou (Chemical Engineering Journal, 2025)

Peroxisomal biogenesis factor 11 as a novel target to trigger lipid biosynthesis and salt stress resistance in oleaginous Tetradesmus obliquus - Yunzhuan Xue; Wei Wang; Xiajule Sheng; Zexu Zheng; Zihan Wang; Fangling Ding; Jinjin Li; Zhiwei Sun; Yu’ang Cai; Xianhua Wang; Jiao Xue (Bioresource Technology, 2025)

Mitochondrial biogenesis microcarriers break membrane barriers for endogenous nucleus pulposus repair - Xiaohu Li; Hongze Chang; Libin Pang; Ang Li; Juan Wang; Yi Yu; Honglei Xiao; Zhengwei Cai; Wenguo Cui; Xiaodong Liu (Chemical Engineering Journal, 2025)

Effects of Ammonia loading and oxygen flux on nitrogen removal in a PNA-coupled MABR - Jiang-Feng Zhang; Jinfeng Bao; Chun-Yu Lai; Chen Zhou; Ang Li; He-Ping Zhao (Journal of Water Process Engineering, 2025)

Analysis of the softening-melting mechanism of cold-bonded briquette from return sinter fines - Ying Li; Dejin Qiu; Manqing Li; Yuandong Xiong; Timo Fabritius; Su Cao; Ang Li; Abdallah Ahmed Elsherbiny; Jie Ren; Han Wei; Yaowei Yu (Journal of Cleaner Production, 2025)

Interfacial built-in electric field in 2D Ni(OH)2 heterojunction with the sodium organic compound for enhanced oxygen evolution catalysis - Jiao Zhou; Mingyuan Zhang; Baiyu Ren; Qian Yi; Hao Yu; Baoyue Zhang; Ang Li; Xinyi Hu; Zhong Li; Guanyu Chen; Yinfen Cheng; Rui Gao; et al. (Chemical Engineering Journal, 2025)

Biogenic amorphous FeOOH activated additional intracellular electron flow pathways for accelerating reductive dechlorination of tetrachloroethylene - Yang Yu; Ang Li; Sheng-Qiang Fan; He-Ping Zhao (Water Research, 2024)

Construction of a synthetic anaerobic dechlorination microbiome to degrade chlorinated ethenes by application of metabolic interactions principle - Zeyi Wang; Yang Yu; Rongjian Zhao; Ang Li (Science of The Total Environment, 2024)

The zinc-finger transcription factor ZFP8 negatively regulates the drought stress response in Arabidopsis thaliana by inhibiting the transcriptional activity of ABF2 - Yu'ang Tian; Yanling Li; Kelan Wang; Ran Xia; Yingru Lin; Guohui Pan; Haoyu Shi; Dawei Zhang; Honghui Lin (Journal of Plant Physiology, 2024)

Rapamycin protects mouse skin from ultraviolet B-induced photodamage by modulating Hspb2-mediated autophagy and apoptosis - Ang Li; Ai-Jun Chen; Jing Xu; Zhu-Yuan Wen; Gen-Long Bai; Zi-Yue Wang; Yu-Xin Jiang; Ping Wang (Molecular Biology Reports, 2024)

Rational regulation of post-electrodialysis electrochromic anion exchange membranes via TiO2@Ag synergistically strengthens visible-light photocatalytic anti-contamination activity - Yuyang Yao; Yueyue Lu; Jingwen Xu; Jiacheng Yu; Liang Guo; Heda Ding; Jian Li; Junbin Liao; Edison Huixiang Ang; Zhenlu Shen; Jiangnan Shen (Water Research, 2024)

Resourceful application and mechanism of oyster shell-microalgae synergistic system：Sustainable treatment of harsh low carbon nitrogen ratio actual wastewater - Yanni Geng; Liming Yang; Chun-Ang Lian; Spyros G. Pavlostathis; Zhiguang Qiu; Zhensheng Xiong; Yuanqi Liu; Bing Li; Jincheng Hu; Wenbo Fan; Xubiao Luo; Ke Yu (Environmental Research, 2024)

Tuning quantum dots emission on DNA tetrahedron/silica nanosphere/graphene oxide nanointerface for ratiometric fluorescence assay of Pb2+ in multiplex samples - Manting Li; Haikun Luo; Zhao Wang; Qian Mo; Shanshan Zhong; Yu-ang Mao; Shuting Li; Xinchun Li (Analytica Chimica Acta, 2024)

Spawning, larval morphological ontogeny and first feeding of yellow-striped cardinalfish Ostorhinchus cyanosoma (Bleeker, 1853) - Ang Lu; Xiang-Yu Li; Yi-Yang Lin; Yen-Ju Pan (Aquaculture, 2024)

Role of inflammatory lipid and fatty acid metabolic abnormalities induced by plastic additives exposure in childhood asthma - Zhiyu Chen; Fang Li; Lei Fu; Yu Xia; Ying Luo; Ang Guo; Xiaona Zhu; Huifang Zhong; Qian Luo (Journal of Environmental Sciences, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

Identification and characterization of a novel Iflavirus in a stored-product psocid, Liposcelis bostrychophila (Psocodea: Liposcelididae) - Peng-Yu Guo; Dan-Dan Wei; Hua-Yue Feng; Xin-Ping Tang; Yu-Ang Chen; Yi Li; Jin-Jun Wang (Journal of Stored Products Research, 2023)

Particulate organic emissions from incense-burning smoke: Chemical compositions and emission characteristics - Kai Song; Rongzhi Tang; Ang Li; Zichao Wan; Yuan Zhang; Yuanzheng Gong; Daqi Lv; Sihua Lu; Yu Tan; Shuyuan Yan; Shichao Yan; Jingshun Zhang; et al. (Science of The Total Environment, 2023)

Fractional model for simulating Long-Term fracture conductivity decay of shale gas and its influences on the well production - Yu Peng; Ang Luo; Yongming Li; Yijia Wu; Wenjun Xu; Kamy Sepehrnoori (Fuel, 2023)

Advances and promotion strategies of membrane-based methods for extracting lithium from brine - Yu-ning Zhang; De-hao Yu; Chen-yu Jia; Li-yue Sun; Ang Tong; Yao Wang; Yan-xin Wang; Lin-jun Huang; Jian-guo Tang (Desalination, 2023)

The thermodynamics of enhanced dope stability of cellulose solution in NaOH solution by urea - Yu Chen; Yoshiharu Nishiyama; Ang Lu; Yan Fang; Ziqiang Shao; Tao Hu; Dongdong Ye; Haisong Qi; Xiaodong Li; Jakob Wohlert; Pan Chen (Carbohydrate Polymers, 2023)

DUSP2 Deletion Inhibits Macrophage Migration by Inhibiting ERK Activation in Zebrafish - Yu-Jiao Li; Xin-Liang Wang; Ling-Yu Shi; Zong-Yi Wang; Zi-Ang Zhao; Shu-Chao Ge; Bing Hu (Fishes, 2023)
Dual-specificity phosphatase 2 (DUSP2) regulates the activation of members of the mitogen-activated protein kinase (MAPK) family, which is involved in a variety of cellular processes including cell proliferation, differentiation, apoptosis, and migration. DUSP2 also regulates the expression of inflammatory mediators in macrophages; however, it remains unknown whether DUSP2 participates in macrophage migration. Here, using the tail fin injury model in zebrafish larvae, we found that the deletion of DUSP2 inhibited the expression of pro-inflammatory cytokines and macrophage chemokines. Moreover, live imaging results showed that the migration of macrophages to the injury site was inhibited after DUSP2 deletion. This inhibitory effect was mediated through the reduced activation of extracellular regulated protein kinases (ERK) in DUSP2 knockout zebrafish.

In situ reductive dehalogenation of groundwater driven by innovative organic carbon source materials: Insights into the organohalide-respiratory electron transport chain - Yang Yu; Yueyan Zhang; Yuqing Liu; Mengran Lv; Zeyi Wang; Li-lian Wen; Ang Li (Journal of Hazardous Materials, 2023)

Piezoelectric energy harvesting and dissipating behaviors of polymer-based piezoelectric composites for nanogenerators and dampers - Wenzheng Chen; Qitan Zheng; Yi Ang Lv; Yujie Chen; Qunfu Fan; Xunhuang Zhou; Hua Li; Qili Yu; Hezhou Liu (Chemical Engineering Journal, 2023)

scRNA-seq analysis reveals toxicity mechanisms in shrimp hemocytes subjected to nitrite stress - QingJian Liang; BeiBei Dong; Ang Li; LiTing Wu; Yu Zhang; Tao Han; Xing Liu (Chemosphere, 2023)

Ionic liquid etched and microwave-assisted delaminated MXene as an excellent electrocatalyst for the hysteretic negative reaction of vanadium redox flow batteries - Minghua Jing; Xi Li; Hao Yu; Xinyu An; Zhuling Liu; Ang Zhang; Xindong Qin; Chao Li; Dawei Fang (Chemical Engineering Journal, 2023)

A feasibility study on the use of hydrophobic eutectic solvents as pseudo-stationary phases in capillary electrophoresis for chiral separations - Ang Li; Song Xue; Yu Xu; Sihui Ding; Di Wen; Qi Zhang (Analytica Chimica Acta, 2023)

Microfluidic preparation of a novel phoxim nanoemulsion pesticide against Spodoptera litura - Zong-Nan Li; Yu-Xuan Zhang; Zhi-Ang Zhang; Lian-Han Pan; Ping Li; Yan Xu; Sheng Sheng; Fu-An Wu; Jun Wang (Environmental Science and Pollution Research, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Identification of structural variation and polymorphisms of a sex co-segregating scaffold in spinach - Li’ang Yu; Xiaokai Ma; William Wadlington; Ray Ming (Plant Reproduction, 2022)

Distinct durability of IgM/IgG antibody responses in COVID-19 patients with differing severity - Junyan Han; Ning Zhang; Danying Chen; Yuhuan Gong; Guoli Li; Yaxian Kong; Lin Pu; Chen Chen; Jingyuan Liu; Qi Wang; Ju Zhang; Xuesen Zhao; et al. (Science China Life Sciences, 2022)

FOXA2 inhibits doxorubicin-induced apoptosis via transcriptionally activating HBP rate-limiting enzyme GFPT1 in HCC cells - Huang Huang; Yuhan Wang; Tianmiao Huang; Lingyan Wang; Yangzhi Liu; Qiong Wu; Ang Yu; Meiyun Shi; Xiaoyu Wang; Wenli Li; Jianing Zhang; Yubo Liu (Journal of Physiology and Biochemistry, 2021)

Dynamic evaluation and spatiotemporal evolution of China’s industrial water use efficiency considering undesirable output - Changfeng Shi; Xinyun Zeng; Qianwen Yu; Junyuan Shen; Ang Li (Environmental Science and Pollution Research, 2021)

Antimonate removal by diatomite modified with Fe-Mn oxides: application and mechanism study - Qiu-Yi Dong; Yu-Chun Fang; Bin Tan; Aura Ontiveros-Valencia; Ang Li; He-Ping Zhao (Environmental Science and Pollution Research, 2021)

Construction of high-density genetic maps defined sex determination region of the Y chromosome in spinach - Li’ang Yu; Xiaokai Ma; Ban Deng; Jingjing Yue; Ray Ming (Molecular Genetics and Genomics, 2021)

Mechanical and Failure Characteristics of Rock-coal-rock Combined Body under Different Strain Rates: A Numerical Study from Micro Perspective - Shu-ning Dong; Ang Li; Ya-dong Ji; Yu-xuan Yang; Qian Mu (Geotechnical and Geological Engineering, 2021)

Numerical Simulation of a Polar Ship Moving in Level Ice Based on a One-Way Coupling Method - Bao-Yu Ni; Zi-Wang Chen; Kai Zhong; Xin-Ang Li; Yan-Zhuo Xue (Journal of Marine Science and Engineering, 2020)
In most previous ice–ship interaction studies involving fluid effects, ice was taken as unbreakable. Building breakable level ice on water domain is still a big challenge in numerical simulation. This paper overcomes this difficulty and presents a numerical modeling of a ship moving in level ice on the water by using a one-way CFD-DEM (computational fluid dynamics-discrete element method) coupling method. The detailed numerical processes and techniques are introduced. The ice crack propagation process including radial and circular cracks have been observed. Numerical results are compared with previous experimental data and good agreement has been achieved. The results show that water resistance is an order of magnitude smaller than ice resistance during the ice-breaking process. Ice resistance shows strong oscillation along with ice failure process, which are affected by ship speed and ice thickness significantly.

OP16 induces deadly autophagy and apoptosis of cells by inhibiting Akt in esophageal squamous cell carcinoma - Guiqin Hou; Ang Jia; Li Yang; Yu Zhao; Yi Hu; Wuduo Zhao; Wen Zhao; Hong-Min Liu; Zhaoming Lu (Molecular and Cellular Biochemistry, 2020)

Litorilituus lipolyticus sp. nov., isolated from intertidal sand of the Yellow Sea in China, and emended description of Colwellia asteriadis - Ang Liu; Yan-Jiao Zhang; Qing-Jie Xue; Hui Wang; Yuan-Yuan Yang; Feng Du; Long-Yu Zhao; Hong-Hua Zhang; Yun-Qing Li; Xiu-Zhen Li (Antonie van Leeuwenhoek, 2020)

Flavivirga rizhaonensis sp. nov., a marine bacterium isolated from intertidal sand - Ang Liu; Hong-Mei Liu; Feng Du; Shuang Wang; Long-Yu Zhao; Hong-Hua Zhang; Yun-Qing Li; Qing-Jie Xue; Xiu-Zhen Li (Antonie van Leeuwenhoek, 2019)

Treatment of Periodontal Bone Defects with Stem Cells from Inflammatory Dental Pulp Tissues in Miniature Swine - Ye Li; Xi Nan; Tian-Yu Zhong; Tong Li; Ang Li (Tissue Engineering and Regenerative Medicine, 2019)

Differential responses of canopy nutrients to experimental drought along a natural aridity gradient - Wentao Luo; Xiaoan Zuo; Wang Ma; Chong Xu; Ang Li; Qiang Yu; Alan K. Knapp; Roberto Tognetti; Feike A. Dijkstra; Mai‐He Li; Guodong Han; Zhengwen Wang; et al. (Ecology, 2018)
The allocation and stoichiometry of plant nutrients in leaves reflect fundamental ecosystem processes, biotic interactions, and environmental drivers such as water availability. Climate change will lead to increases in drought severity and frequency, but how canopy nutrients will respond to drought, and how these responses may vary with community composition along aridity gradients is poorly understood. We experimentally addressed this issue by reducing precipitation amounts by 66% during two consecutive growing seasons at three sites located along a natural aridity gradient. This allowed us to assess drought effects on canopy nitrogen (N) and phosphorus (P) concentrations in arid and semiarid grasslands of northern China. Along the aridity gradient, canopy nutrient concentrations were positively related to aridity, with this pattern was driven primarily by species turnover (i.e., an increase in the relative biomass of N‐ and P‐rich species with increasing aridity). In contrast, drought imposed experimentally increased N but decreased P concentrations in plant canopies. These changes were driven by the combined effects of species turnover and intraspecific variation in leaf nutrient concentrations. In addition, the sensitivity of canopy N and P concentrations to drought varied across the three sites. Canopy nutrient concentrations were less affected by drought at drier than wetter sites, because of the opposing effects of species turnover and intraspecific variation, as well as greater drought tolerance for nutrient‐rich species. These contrasting effects of long‐term aridity vs. short‐term drought on canopy nutrient concentrations, as well as differing sensitivities among sites in the same grassland biome, highlight the challenge of predicting ecosystem responses to future climate change.

Influence of heterogeneity on mechanical and acoustic emission behaviours of stratified rock specimens - Ang Li; Guo-jian Shao; Jing-bo Su; Yang Sun; Tian-tang Yu; Hou-gai Shi (European Journal of Environmental and Civil Engineering, 2018)

Long-term variation in the salinity of the Southern Yellow Sea Cold Water Mass, 1976–2006 - Ang Li; Fei Yu; Guangcheng Si; Chuanjie Wei (Journal of Oceanography, 2017)

Prescreening, identification and harvesting of microalgae with antibacterial activity - Ang Li; Ling Zhang; Zhen-yu Zhao; Sha-sha Ma; Meng Wang; Ping-huai Liu (Biologia, 2016)

Transcriptome Sequencing of the Sweet Potato Progenitor (Ipomoea Trifida (H.B.K.) G. Don.) and Discovery of Drought Tolerance Genes - Qinghe Cao; Ang Li; Jinyang Chen; Yu Sun; Jun Tang; An Zhang; Zhilin Zhou; Donglan Zhao; Daifu Ma; Shan Gao (Tropical Plant Biology, 2016)

Early–middle Holocene hydroclimate changes in the Asian monsoon margin of northwest China inferred from Huahai terminal lake records - Zhuolun Li; Nai’ang Wang; Hongyi Cheng; Yu Li (Journal of Paleolimnology, 2016)

Association Between a Variant in ADAMTS5 and the Susceptibility to Hepatocellular Carcinoma in a Chinese Han Population - Chongyi Li; Yanli Xiong; Zhaoyang Zhong; Shiheng Zhang; Yu Peng; Lin’ang Wang; Nan Dai; Mengxia Li; Tao Ren; Lixia Gan; Dong Wang (Cell Biochemistry and Biophysics, 2015)

Carbonate formation and water level changes in a paleo-lake and its implication for carbon cycle and climate change, arid China - Yu Li; Nai’ang Wang; Zhuolun Li; Xuehua Zhou; Chengqi Zhang; Yue Wang (Frontiers of Earth Science, 2013)

Climatic and environmental change in Yanchi Lake, Northwest China since the Late Glacial: A comprehensive analysis of lake sediments - Yu Li; Nai’ang Wang; Zhuolun Li; Xuehua Zhou; Chengqi Zhang (Journal of Geographical Sciences, 2013)

Isolation and characterization of polymorphic microsatellite markers in the fish Garra orientalis (oriental sucking barb) - Li-Wei Su; Zhi-Zhi Liu; Cong-Tao Wang; Zhen Zeng; Ang-Yu Liu; Wen-Qiao Tang; Jin-Quan Yang (Conservation Genetics Resources, 2013)

Lake evaporation: A possible factor affecting lake level changes tested by modern observational data in arid and semi-arid China - Yu Li; Nai’ang Wang; Zhuolun Li; Ning Ma; Xuehua Zhou; Chengqi Zhang (Journal of Geographical Sciences, 2013)

Tree‐ring‐based temperature reconstruction for the northern Greater Higgnan Mountains, China, since A.D. 1717 - Tongwen Zhang; Yujiang Yuan; Wenshou Wei; Shulong Yu; Ruibo Zhang; Huaming Shang; Feng Chen; Zi'ang Fan; Li Qin (International Journal of Climatology, 2013)
In this paper, ring‐width chronologies of pine trees ( Pinus sylvestris var. mongolica ) from one sampling site in the northern Greater Higgnan Mountains, China, were constructed. The results of growth‐climate responses show that mean temperature is the limiting factor affecting radial growth of pine trees in the study area. Consequently, mean temperature from May to October from 1717 to 2008 has been reconstructed using the standard chronology. For the calibrated period (1957‐2008), the explained variance of the reconstruction is 57%. The characteristics of the reconstruction expose that mean temperature has increased since the 1970s, and the decade 2000s and 1990s are also ranked as the warm decades on record. However, this period from 1970s to now is not exceptional within the past 300 years. By applying an 11‐year moving average to the reconstruction, three warm periods and three cold periods are evident. The warm and cold periods of the reconstructed mean temperature correspond well with other reconstructions. Power spectral and wavelet analysis demonstrated the existence of significant ∼70‐ and ∼100‐year cycles of variability. Furthermore, the reconstruction and North Atlantic Oscillation Index showed a significant positive correlation ( r = 0.34, n = 136, p

Holocene climate cycles in northwest margin of Asian monsoon - Yu Li; Nai’ang Wang; Zhuolun Li; Xuehua Zhou; Chengqi Zhang (Chinese Geographical Science, 2012)

Temperature reconstruction from tree-ring maximum latewood density of Qinghai spruce in middle Hexi Corridor, China - Feng Chen; Yu-jiang Yuan; Wen-shou Wei; Shu-long Yu; Zi-ang Fan; Rui-bo Zhang; Tong-wen Zhang; Qin Li; Hua-ming Shang (Theoretical and Applied Climatology, 2012)

Characterization of a compound bioflocculant produced by mixed culture of Rhizobium radiobacter F2 and Bacillus sphaeicus F6 - Lili Wang; Fang Ma; Yuanyuan Qu; Dezhi Sun; Ang Li; Jingbo Guo; Bing Yu (World Journal of Microbiology and Biotechnology, 2011)

Study on algorithms of low SNR inversion of T 2 spectrum in NMR - Feng Lin; Zhu-Wen Wang; Jing-Ye Li; Xue-Ang Zhang; Yu-Long Jiang (Applied Geophysics, 2011)